Model Kualitas Pelayanan Penerbitan Surat Tanda Nomor Kendaraan Bermotor Di Kantor Sistem Administrasi Manunggal Satu Atap Kabupaten Bulukumba - Syamsir, Syamsir; Ansari, Muh Isa; Haerana, Haerana (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
The purpose of this study was to find out how the quality of service issuance of motorized vehicle number certificates in the one-stop administrative system office in Bulukumba district. This type of research used in this research is descriptive qualitative research. Data collection techniques used by researchers are observation, interviews with the amount of information as many as 7 people. Data analysis techniques used are data reduction, data presentation and conclusion drawing. The validity of the data used triangulation namely time triangulation, source triangulation and technical triangulation.The results of this study can be seen that the service of publishing motor vehicle number signs in the office of the one-stop administrative system in Bulukumba district has been running in accordance with applicable and optimal procedures. With appropriate services and not convoluted, it really helps the community in solving the vehicle tax problem in Bulukumba district.